Adaptive AI Systems for Tailoring Learning Resources in Libraries - Mohammed, H.F.; Chidambaram, K.R.; Aruna, V.; Harita, U.; Ugli, Bekmirzayev Mirjalol Xusanboy; Kalidoss, D. (Indian Journal of Information Sources and Services, 2026)
As libraries transition from physical learning environments to more prevalent technologies that incorporate AI, they face newfound challenges, as well as solve emerging problems with the aid of adaptive AI. In this research project, we will describe the proposed strategies for integrating and implementing adaptive AI in libraries. We explain how we design the system, its advantages, and its disadvantages of adaptive AI applications in educational library systems. Like with other learning resource repositories, libraries are embracing adaptive AI technology to enhance access and interaction by offering personalized resource recommendations based on user skills, interests, behaviors, and personal tendencies. This improves the knowledge-gaining process among users while also making it easier for educators to analyze the effectiveness of advanced learning technologies. Diaries are not only developing learning analytics but also significantly improving the learning process by encouraging the use of videos in classes. AI can also be used to classify large volumes of online content and maintain extensive teaching collections, thus making these materials readily available through the use of advanced natural language processing and machine learning algorithms. The dynamic AI, which these works imply, may transform materials into various forms, including texts, graphics, audio, and videos, allowing different learners to grasp the material. Adaptive AI not only encourages participation but also teaches history by offering dynamic, inclusive, and real-time recommendations by participation improvement engines, which structure effortless directions, promoting responsive, customized environments with sophisticated algorithms and the involvement of an underlying level.